2020
DOI: 10.1016/j.trecan.2019.11.010
|View full text |Cite|
|
Sign up to set email alerts
|

Tumor Functional Heterogeneity Unraveled by scRNA-seq Technologies

Abstract: Effective cancer treatment has been precluded by the presence of various forms of intratumoral complexity that drive treatment resistance and metastasis. Recent single-cell sequencing technologies are significantly facilitating the characterization of tumor internal architecture during disease progression. New applications and advances occurring at a fast pace predict an imminent broad application of these technologies in many research areas. As occurred with next-generation sequencing (NGS) technologies, once… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
99
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(111 citation statements)
references
References 57 publications
0
99
0
1
Order By: Relevance
“…As future works, we will further explore our approach in its ability to model massive scale singlecell sequencing data including cross-species, multi-omics (e.g., simultaneously modeling singlecell RNA-seq, single-cell ATAC-seq, and single-cell methylation while accounting for platformdependent batch effects), multi-tissues, and multi-subjects. We will harness recently available human/mouse atlas data [41,42] and disease-focused data such as scRNA-seq in patients with Alzheimer's disease [6] and cancer patients tumors [45]. From methodological stand-point, like all of the neural network-based method, scGAN requires specification of the network architecture before training.…”
Section: Discussionmentioning
confidence: 99%
“…As future works, we will further explore our approach in its ability to model massive scale singlecell sequencing data including cross-species, multi-omics (e.g., simultaneously modeling singlecell RNA-seq, single-cell ATAC-seq, and single-cell methylation while accounting for platformdependent batch effects), multi-tissues, and multi-subjects. We will harness recently available human/mouse atlas data [41,42] and disease-focused data such as scRNA-seq in patients with Alzheimer's disease [6] and cancer patients tumors [45]. From methodological stand-point, like all of the neural network-based method, scGAN requires specification of the network architecture before training.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors contain different cell populations in endless evolution. This diversity is commonly referred to as tumor heterogeneity, and is considered the main driver of resistance to therapy and metastasis (106). The full comprehension of this heterogeneity would be extremely important to optimize existing therapeutic intervention and find new strategies to break down relapses and mortality.…”
Section: Immune Cells In the Tumor Microenvironmentmentioning
confidence: 99%
“…The recent development of technologies based on sequencing individual cells has been crucial to address tumor heterogeneity and to elucidate how cells are organized into multicellular systems. Single cell profiles not only revealed that human tumors comprise subpopulations of genetically different diverse malignant cells, but also that a profusion of different cell types from the surrounding tissues and the immune system, each with a precise role in pathogenicity, is present within the TME (106,107). The immune components of the tumor microenvironment in different kind of malignancies, including non-small cell lung cancer (NSCLC), clear cell RCC (ccRCC), breast cancer (BC), HCC, glioblastoma multiforme (GMB), microsatellite instability-stable CRC have been recently annotated and finely characterized (88,(108)(109)(110)(111).…”
Section: Immune Cells In the Tumor Microenvironmentmentioning
confidence: 99%
“…Single-cell RNA sequencing (scRNA-seq) is a powerful tool to study development, tissue, and disease biology [1][2][3][4][5][6][7][8][9] . scRNA-seq analyses currently rely on the availability of high quality genome annotations to define cell features and to perform cell clustering, dimensionality reduction, differential gene expression, and other analyses [10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%